TRANSLATION OF VIETNAMESE CONTRACTS FOR DISTRIBUTION OF THE SUCCESSION ESTATE INTO POLISH - NOWICKI, Bogdan (Comparative Legilinguistics, 2016)
Vietnamese-Polish and Polish-Vietnamese legal translation is rarely discussed in pertinent literature. One of the documents which are executed in legal transactions in family law are contracts for the distribution of the succession estate. The increasing number of marriages concluded between Polish and Vietnamese citizens makes this type of document of interest of translators. The following research methods have been applied: (i) analysis of comparable texts, (ii) techniques of providing equivalents for non-equivalent or partially equivalent terms and syntagms, and (iii) methods of translation applicable to sentences. The comparison of Vietnamese and Polish contracts for the distribution of the succession estate has revealed significant similarities at the syntactic and semantic level.